Detection of COVID-19 virus using deep learning. (15th March 2022) - Mehta, Kewal; Patel, Hritik; Patel, Vraj; Sharma, Ankit K.
Corona Virus Disease of 2019 (COVID-19) is currently the most threatening and major medical challenge in the world. COVID-19 can be detected using X-ray and CT-scan images of the patient's lungs. With the use of deep learning and neural networks, the process of classifying the patient's CT-scan and X-ray images can be expedited. In this paper, we implemented convolutional neural networks (CNN) for detection of COVID-19 in X-ray and CT-scan images of lungs. Several CNN architectures like VGG16, ResNet-50, Inception-v3, DenseNet 201, Xception, and InceptionResnet-v2 have been implemented and comparative analysis is presented. DenseNet 201 CNN architecture is found to be most accurate in detecting COVID-19 for both X-ray and CT-scan images. The quantitative results suggest promising results for the COVID-19 detection task.